Motion control algorithm development and testing for a free-piston engine generator - Hanipah, M. Razali
Free-piston engine generator has the potential to provide a compact and efficient power generator for hybrid electric vehicles. This research aims objectives to construct simulation model of a free-piston linear generator for piston motion control algorithm development and testing on a linear actuators prototype. To achieve these objectives, a survey on several motion control technologies was done. Concurrently, a multi-domain free-piston engine generator model was developed for the project. Preliminary results of the model were used for technical specifications requirement for developing the linear actuator test rig. Upon completing the model development, a motion control simulation was conducted. This model is subjected to stability test which was measured in terms of mathematical convergent. Next, the suitable motion control was implemented and tested on the linear actuator setup. From the analysis, the changes of disturbance of the electromagnetic force in acceleration and deceleration stages could improve the piston acceleration and hence increase the average velocity. The trapezoidal motion profile is able to move the piston to the targeted stroke of 33mm and 38mm. However, the final position produced via S-curve motion profile is 18% shorter due to the slower ascend and descend during the first and final 20% of the cyclic duration. A complete linear actuator prototype driven by air compressor was completed and tested.